2020
DOI: 10.1186/s13059-020-02186-x
|View full text |Cite
|
Sign up to set email alerts
|

Cis-acting lnc-eRNA SEELA directly binds histone H4 to promote histone recognition and leukemia progression

Abstract: Background Long noncoding enhancer RNAs (lnc-eRNAs) are a subset of stable eRNAs identified from annotated lncRNAs. They might act as enhancer activity-related therapeutic targets in cancer. However, the underlying mechanism of epigenetic activation and their function in cancer initiation and progression remain largely unknown. Results We identify a set of lncRNAs as lnc-eRNAs according to the epigenetic signatures of enhancers. We s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 70 publications
(78 reference statements)
0
14
0
Order By: Relevance
“…Additionally, Fang et al. ( 160 ) found that eRNAs such as SEELA are widely activated in mixed-lineage leukaemia and demonstrated that SEELA directly binds to amino acid K31 of histone 4 and mediates the cis-activated transcription of the neighboring oncogene serine incorporate 2, which regulates oncogene transcription and tumour metabolism (sphingolipid synthesis) to influence leukaemia progression. The demethylation of vascular endothelial growth factor A (VEGFA) enhancer in CML promotes the overexpression of cancer signature genes.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, Fang et al. ( 160 ) found that eRNAs such as SEELA are widely activated in mixed-lineage leukaemia and demonstrated that SEELA directly binds to amino acid K31 of histone 4 and mediates the cis-activated transcription of the neighboring oncogene serine incorporate 2, which regulates oncogene transcription and tumour metabolism (sphingolipid synthesis) to influence leukaemia progression. The demethylation of vascular endothelial growth factor A (VEGFA) enhancer in CML promotes the overexpression of cancer signature genes.…”
Section: Resultsmentioning
confidence: 99%
“…Protein recombination and purification were performed as described previously 22 , 38 . Briefly, recombinant proteins were expressed in E. coli strain BL21 [Transetta (DE3) chemically competent cell (Transgen biotech, CD801)].…”
Section: Methodsmentioning
confidence: 99%
“…LncRNAs can play a role in cancer development by directing histone-modifying enzymes to regulate the methylation and acetylation status of histones and cis-regulating the expression of nearby genes ( 24 , 98 , 99 ). For example, lncRNA EZR-AS1 recruits H3K4 methyltransferase SMYD3 to catalyze Tri-methylation of lysine 4 on histone H3 (H3K4me3) at the EZR promoter.…”
Section: Lncrnas Regulate Other Epigenetic Modalities Through Rbpsmentioning
confidence: 99%